The Influence of Fadil Jaidi Influencer Attractiveness on Brand Engagement in Self-Concept, Brand Expected Values and Purchase Intentions on Recommended Products - Larasati Amanda Nurfadilah; Erlita Ridanasti (Jurnal Economic Resource, 2023)
Influencer marketing is considered a form of endorsement using the influencer's product recommendations to drive sales, but its purported purpose involves a much broader outcome of getting the attention of potential customers, generating word of mouth, and creating customer engagement with a brand or product. This research is based on Observational Learning Theory which explains new individual learning behavior by observing other people and the consequences of their actions. This study aims to determine whether influencer attractiveness has an influence on brand engagement in self-concept, the expected value of the brand and the purchase intention of the recommended brand. The method used is the structural structural model (SEM) to distribute samples from a total of 220 respondents in the questionnaire. Testing was carried out using the IBM SPSS 25 program and SmartPLS ver 4.0 software. The results of this study indicate that the rejection of one of the hypotheses that attracts influencer attractiveness has a positive but not significant effect on the intention to buy the recommended brand.